Susceptibility vessel sign on T2* magnetic resonance imaging and recanalization results of mechanical thrombectomy with stent retrievers: a multicentre cohort study. (19th March 2015) - Soize, S.; Batista, A. L.; Rodriguez Regent, C.; Trystram, D.; Tisserand, M.; Turc, G.; Serre, I.; Ben Hassen, W.; Zuber, M.; Calvet, D.; Mas, J.‐L.; Meder, J.‐F.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose The susceptibility vessel sign (SVS) on T2*‐weighted magnetic resonance imaging has been reported in several studies as a negative predictor of early recanalization after intravenous thrombolysis. The meaning of SVS regarding the results of mechanical thrombectomy with stent retrievers was investigated. Methods Susceptibility vessel sign presence and length were studied in 153 acute ischaemic stroke patients (82 men; mean ± SD age 59 ± 17 years, baseline National Institutes of Health Stroke Scale score 17.2 ± 6.5) from three stroke centres, treated with either mechanical thrombectomy alone (n = 84) or bridging therapy (n = 69). Variables were compared between recanalizers, defined as thrombolysis in cerebral infarction (TICI) scores ≥2b, and non‐recanalizers (TICI<2b). Results The SVS was present in 113 (73.8%) patients. There was no association between the presence of SVS and recanalization, obtained in 86 (56.2%) patients, in the whole population [odds ratio (OR) 1.24, 95% confidence interval (CI) 0.53–2.92, P = 0.84) and in treatment subgroups (bridging: OR = 0.91, 95% CI 0.29–2.87, P = 1.0; thrombectomy alone: OR = 1.85, 95% CI 0.48–7.16, P = 0.54). However, in SVS+ patients, recanalization decreased with SVS length (OR 0.94 for each additional mm, 95% CI 0.89–0.99; P = 0.02). Conclusions The success of recanalization in acute stroke patients treated with stent retrievers was related to thrombus length but not to the presence of SVS.